Pengaruh Pengangaran Berbasis Kinerja, Pengawasan Preventif dan Pengawasan Detektif Terhadap Efektifitas Pengendalian Anggaran (Studi Empiris Pada Satuan Kerja Perangkat Daerah di Kabupaten Pelalawan) - Pratama, Dafitra; ', Desmiyawati; ', Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the Effects of Performance-Based Budgeting, Monitoring and Control Preventive Detective on Budgetary Control Effectiveness survey on the Lokal Government unit (SKPD) district at Pelalawan of Riau province as the research object. The population used in this study was 26 on the Lokal Government unit (SKPD) district at Pelalawan of Riau Province, the sample is in the Environment Agency and the Department SKPD district at Pelalawan of Riau Province with 82 respondents consisting of Echelon III and IV. This type of data is the primary data collection method of data using questionnaires. The method of data analysis used in this study is multiple regression ( multiple regression ) with the help of SPSS software version 19.0. The results of this study indicate that the variable performance-based budgeting does not effect the effectiveness of the Budget Control has a value of 0.079 with a significant regression coefficient of 0.418 (P> 0.05), no effect Preventive Monitoring the effectiveness of the budgetary control has a value of 0.023 with a regression coefficient of 0.532 significant ( p > 0.05 ), Surveillance Detective has a value of 0.422 with a significant regression coefficient of 0.000 ( p < 0.05 ) effect on Budgetary Control Effectiveness. Rated R square of 0.342 ( 34.2 % ) of independent variables in this study were able to influence the dependent variable. 0.658 while the rest ( 65.8 % ) describe other independent variables that are not observed in this study.Keywords: Performance-Based Budgeting, Monitoring Preventive, Detective Control, Budgetary Control Effectiveness.